(3eMGhdI fMh fXQjI YGeI dMb GdedcjI(B: s (3fGUQ eMeO YHOGddg SdWGf(B.s - (3fGUQ eMeO YHOGddg SdWGfs; (3fRjI eMeO GdUGOb GdegOis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3Gf GdYed GdPgfi YHGQI Yf eUfa eHJcQ ai eLGd GdOH Gh Gdafhf Gh GdYdhe h jJQJH Ydi Pdc GfI dGHO ef Gf jXgQ GdeUfa Gdi MjR GdhLhO ai Tcd eMShS h Gf jchf PG WGHY GHOGYi jfe Yf GdGHJcGQ h JbSe GdeUfaGJ Gdi fhYjf QFjSjf geG GdeUfaGJ GdGUdjI h GdeUfaGJ GdeTJbI h jYO GdeUfa GUdjG eJi GfTGI GdeDdas
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2007s
(3HHdjhLQGajG(B: (3UaMGJ (B430-459s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdeUfaGJ GdGOHjIs; (3Mb GdedcjIs; (3Mbhb GdeDdas; (3GdYed GdPgfi s; (3JWHjbGJ Mb Gdehda s; (3YbO NOeg GdeYdheGJ GdUhJjg s; (3HWGbg GdGFJeGf GdeUQajg s; (3GdeUfaGJ GdMOjKg s; (3GdWHjYg GdbGfhfjg dMb Gdehda s; (3JGdja GdTNU GdeYfhi s; (3Gdehda GdGLjQ s; (3JYOO Gdehdajf s; (3GdJGdja GdeTJQc s; (3YbO GdfTQ s; (3GdMb GdGOHi ddehda s; (3GdMb GdeGdi ddehdas; (3GdbGfhf GdGeGQGJi s; (3GdMeGjg GdbGfhfjg ddeUfaGJs; (3YbO HQGeM GdMGSH GdGdi s; (3GdMb GdGOHi ddehda s; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs